2002
DOI: 10.1289/ehp.0211043
|View full text |Cite
|
Sign up to set email alerts
|

Air conditioning and source-specific particles as modifiers of the effect of PM(10) on hospital admissions for heart and lung disease.

Abstract: In the last decade, epidemiologic studies have documented associations between particulate matter (PM) air pollution and increases in hospital admissions for respiratory and cardiovascular disease in studies all over the world (1-4). The magnitude of the estimated PM 10 effects, however, has differed substantially among different studies. A recent multicity study, conducted in 14 cities thoughout the United States, has documented significant heterogeneity among the city-specific effect estimates (5). This hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
3
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(131 citation statements)
references
References 23 publications
5
120
3
3
Order By: Relevance
“…Several studies have used source apportionment to estimate source-specific effects of particles (Laden et al, 2000;Mar et al, 2000Mar et al, , 2006Janssen et al, 2002;Lippmann et al, 2005;Ito et al, 2006;Lanki et al, 2006). These studies have consistently showed that particles from motor vehicles and/or long-range transported secondary sulfate were significantly associated with adverse human health including increased total and cardiovascular mortality and hospital admissions, and depressed cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used source apportionment to estimate source-specific effects of particles (Laden et al, 2000;Mar et al, 2000Mar et al, , 2006Janssen et al, 2002;Lippmann et al, 2005;Ito et al, 2006;Lanki et al, 2006). These studies have consistently showed that particles from motor vehicles and/or long-range transported secondary sulfate were significantly associated with adverse human health including increased total and cardiovascular mortality and hospital admissions, and depressed cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Differences would be expected to be greater restricting the analysis to working adults and weekdays. Recent analyses have indicated that housing characteristics such as air conditioning reduce risks of morbidity and mortality associated with outdoor air pollution (Levy et al, 2000(Levy et al, , 2005Janssen et al, 2002), suggesting that this type of environment is in fact protective. In addition, in some instances, advice to reduce the intensity and duration of outdoor physical activity is warranted both in relation to extreme heat and smog, which often coincide.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is likely that a it varies over time and across populations, it will be essential to better characterize this parameter. For instance, Janssen et al (2002) discuss how city-specific estimates of ab vary by prevalence of air conditioning use, an important determinant of population-average ambient attenuation.…”
Section: Implications Of the Measurement Error Model In Time Series Smentioning
confidence: 99%